How to Make Nothing Out of Something: Analyses of the Impact of Study Sampling and Statistical Interpretation in Misleading Meta-Analytic Conclusions - Cunningham, Michael R.; Baumeister, Roy F. (Frontiers in Psychology, 2016)
The limited resource model states that self-control is governed by a relatively finite set of inner resources on which people draw when exerting willpower. Once self-control resources have been used up or depleted, they are less available for other self-control tasks, leading to a decrement in subsequent self-control success. The depletion effect has been studied for over 20 years, tested or extended in more than 600 studies, and supported in an independent meta-analysis (Hagger, Wood, Stiff, and Chatzisarantis, 2010). Meta-analyses are supposed to reduce bias in literature reviews. Carter, Kofler, Forster, and McCullough’s (2015) meta-analysis, by contrast, included a series of questionable decisions involving sampling, methods, and data analysis. We provide quantitative analyses of key sampling issues: exclusion of many of the best depletion studies based on idiosyncratic criteria and the emphasis on mini meta-analyses with low statistical power as opposed to the overall depletion effect. We discuss two key methodological issues: failure to code for research quality, and the quantitative impact of weak studies by novice researchers. We discuss two key data analysis issues: questionable interpretation of the results of trim and fill and funnel plot asymmetry test procedures, and the use and misinterpretation of the untested Precision Effect Test [PET] and Precision Effect Estimate with Standard Error (PEESE) procedures. Despite these serious problems, the Carter et al. meta-analysis results actually indicate that there is a real depletion effect – contrary to their title.